The Sinocyclocheilus cavefish genome provides insights into cave adaptation. Issue 1 (December 2016) - Yang, Junxing; Chen, Xiaoli; Bai, Jie; Fang, Dongming; Qiu, Ying; Jiang, Wansheng; Yuan, Hui; Bian, Chao; Lu, Jiang; He, Shiyang; Pan, Xiaofu; Zhang, Yaolei; et al.
Abstract Background An emerging cavefish model, the cyprinid genusSinocyclocheilus, is endemic to the massive southwestern karst area adjacent to the Qinghai-Tibetan Plateau of China. In order to understand whether orogeny influenced the evolution of these species, and how genomes change under isolation, especially in subterranean habitats, we performed whole-genome sequencing and comparative analyses of three species in this genus, S. grahami, S. rhinocerous andS. anshuiensis . These species are surface-dwelling, semi-cave-dwelling and cave-restricted, respectively. Results The assembled genome sizes ofS. grahami, S. rhinocerous andS. anshuiensis are 1.75 Gb, 1.73 Gb and 1.68 Gb, respectively. Divergence time and population history analyses of these species reveal that their speciation and population dynamics are correlated with the different stages of uplifting of the Qinghai-Tibetan Plateau. We carried out comparative analyses of these genomes and found that many genetic changes, such as gene loss (e.g. opsin genes), pseudogenes (e.g. crystallin genes), mutations (e.g. melanogenesis-related genes), deletions (e.g. scale-related genes) and down-regulation (e.g. circadian rhythm pathway genes), are possibly associated with the regressive features (such as eye degeneration, albinism, rudimentary scales and lack of circadian rhythms), and that some gene expansion (e.g. taste-related transcription factor gene) may point to the constructive features (such as enhanced taste buds) which evolved in these cave fishes. Conclusion As the first report on cavefish genomes among distinct species inSinocyclocheilus, our work provides not only insights into genetic mechanisms of cave adaptation, but also represents a fundamental resource for a better understanding of cavefish biology.